The settlers - Moberg, Vilhelm, 1898-1973 (Moberg, Vilhelm, 1898-1973. Romanen om utvandrarna., 1995)
Karl Oskar and Kristina Nilsson struggle to prosper on their new farm in Minnesota during the 1850s. Kristina, coping with a feeling of loss for Sweden and the difficulty of adapting to a new land, draws strength from a new found spirituality. Karl Oskar brings more land under cultivation and harvests rye, wheat, and corn. Together they survive blizzards, grasshopper plagues, wildcat speculation in currnecy, and self-righteous neighbors.